2001
DOI: 10.1111/0272-4332.214142
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tuberculosis Risk and Incidence under Upper Room Ultraviolet Germicidal Irradiation in a Waiting Room in a Hypothetical Scenario

Abstract: Environmental control measures (ventilation, high-efficiency particulate air filtration, and upper room ultraviolet germicidal irradiation [UVGI]) are recommended to effectively control tuberculosis (TB) transmission from unsuspected TB patients in high-risk settings, but the effectiveness of their use is not often clear. This study presents a simulation model for a hypothetical hospital waiting room, in which the number of susceptible immunocompetent people in the waiting room follows a Poisson distribution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…A mechanical ventilation system in this ward was estimated to produce 402 m 3 /h (range 330-1,209), with high-efficiency particulate air (HEPA) supplementation further increasing effective ventilation by a factor of 3.37 and ultraviolet germicidal irradiation (UVGI) supplementation increasing effective ventilation by a factor of 10.31 above the unsupplemented system [8,[61][62][63][64][65]. Upper-room UVGI in a waiting area alone was not simulated because of the absence of data that could be extrapolated to the simulated hospital [66]. Triangular distributions were constructed for sampling, according to the mean and range of the ventilation rate.…”
Section: 2a-ventilation Improvements Alter the Denominator Of The mentioning
confidence: 99%
“…A mechanical ventilation system in this ward was estimated to produce 402 m 3 /h (range 330-1,209), with high-efficiency particulate air (HEPA) supplementation further increasing effective ventilation by a factor of 3.37 and ultraviolet germicidal irradiation (UVGI) supplementation increasing effective ventilation by a factor of 10.31 above the unsupplemented system [8,[61][62][63][64][65]. Upper-room UVGI in a waiting area alone was not simulated because of the absence of data that could be extrapolated to the simulated hospital [66]. Triangular distributions were constructed for sampling, according to the mean and range of the ventilation rate.…”
Section: 2a-ventilation Improvements Alter the Denominator Of The mentioning
confidence: 99%
“…The Wells-Riley mathematical model has been used to estimate airborne TB infection risk in an enclosed space [7][8][9][10]. The spread of TB infection in an Internet café used by an unspecified number of people is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Energy data on UV systems is limited, but a small number of studies have carried out calculations to explore benefits. Ko et al [8] consider the effectiveness of UV against TB transmission in a waiting room and calculate that UV may be less expensive than increased ventilation by between 3 and 13 times [46]. We recently conducted a modelling study [9] that suggested that installation of UV can achieve reductions in airborne risk comparable to or better than increasing the ventilation rate from 3 to 6 ACH at 11-55% of the energy cost, depending on the scenario.…”
Section: Design Issuesmentioning
confidence: 99%
“…However there is increasing awareness of the relationship between ventilation rate and energy consumption; up to 44% of energy in UK hospitals is thought to be consumed by ventilation and space heating [7]. Studies have suggested that air cleaning technologies may offer the potential to reduce airborne infection risk without the energy costs associated with higher ventilation rates [8,9].…”
Section: Introductionmentioning
confidence: 99%